821Surrounding greenness is associated with slower biological ageing based on epigenetics. (2nd September 2021) - Xu, Rongbin; Li, Shuai; Li, Shanshan; Abramson, Michael; Hopper, John; Guo, Yuming
Abstract: Background: High surrounding greenness has many health benefits, but few studies have evaluated these from the perspective of epigenetics. Methods: We derived Horvath's DNA methylation age (DNAmAge), Hannum's DNAmAge, PhenoAge, and GrimAge from DNA methylation data measured from peripheral blood samples of 479 Australian women in 130 families. The DNA methylation age acceleration (DNAmAgeAC) was calculated as the residuals after regressing DNAmAge on chronological age. Greenness was represented by the satellite-derived Normalized Difference Vegetation Index (NDVI) and Enhanced Vegetation Index (EVI) within 300m, 500m, 1000m and 2000m surrounding participants' home addresses. The greenness-DNAmAgeAC association was evaluated using a within-sibship design fitted by linear mixed effect models, adjusting for familial clustering and important covariates. Results: Our analyses based on the whole sample suggested that the greenness-DNAmAgeAC association was only statistically significant for GrimAge acceleration. Each inter-quartile range (IQR) increase in NDVI within 1000m was associated with 0.59 (95% CI: 0.18, 1.01) year decrease in GrimAge acceleration. Greenness was also inversely associated with GrimAge's three DNA methylation based components (cystatin-C, growth differentiation factor 15, and smoking pack-years). For participants at higher 50% area-level socioeconomic status (SES), each IQR increase in NDVI within 1000m was associated with 1.24 (95%CI: 0.39, 2.09) year and 0.79 (95%CI: 0.29, 1.30) year decrease in Hannum's DNAmAgeAC and GrimAge acceleration, respectively. Conclusions: Higher surrounding greenness was associated with slower biological aging measured by GrimAge acceleration and Hannun's DNAmAgeAC in Australian women, particularly among those who lived in areas at higher SES. Key messages: Epigenetics provides a potential mechanism for why surrounding greenness is an important health issue for community construction.